2014
DOI: 10.4291/wjgp.v5.i1.33
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiology as a tool to unravel the origin of pancreatic pain

Abstract: Intense abdominal pain is the most common symptom in chronic pancreatitis, but the underlying mechanisms are not completely understood and pain management remains a significant clinical challenge. The focus of pain origin in chronic pancreatitis traditionally has been on the pancreatic gland, assuming pain to originate in the pancreas or its surrounding organs. However, research in the last decade points to abnormal central nervous system pain processing. For this reason, electroencephalography has been receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…Interference of chronic pain on cognitive performance has also been examined by qEEG [ 67 ]. Data suggest that qEEG associated with sensoriomotor standardized protocols can help to improve the diagnosis of the mechanisms involved in the chronification process of pain over time [ 2 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interference of chronic pain on cognitive performance has also been examined by qEEG [ 67 ]. Data suggest that qEEG associated with sensoriomotor standardized protocols can help to improve the diagnosis of the mechanisms involved in the chronification process of pain over time [ 2 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have repeatedly suggested that this phenomenon is fundamental for the chronification of pain symptoms [ 6 ]. Quantitative EEG may be used not only to identify some aspects of maladaptive plasticity, but it may also be a feasible, low cost alternative in the management of patients with chronic pain [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These phenomena are closely associated with increased abdominal pain sensation in the respective patients (8). Of note is that the central nervous system might also play a role in pain sensation in CP (27). The detailed mechanism needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, standard clinical and sensory testing, neuroimaging (e.g. Alomar and Bakhaidar, ; Morton et al., ) and electrophysiological (Lelic et al., ; Pinheiro et al., ) assessments have been suggested as tools for evaluating sensitisation processes, but these options are not further discussed in the present paper.…”
Section: Defining and Assessing Sensitisationmentioning
confidence: 99%